Modern management solutions for logistics, finance and human resources in defense and security services - Kuck, J. (Lviv Politechnic Publishing House, 2017)
The aim of the paper is to present the research analysis and author’s practical experiences in implementing modern IT solutions. These solutions concern, in particular building and implementing the Integrated Multilevel IT Systems for Logistics, Finance and HR operating in the defense and security services. The detailed research was also on possibility of implementing systems for product coding, electronic shopping and distance learning. Implementing modern IT solutions should improve performance in logistics, finance and HR in defense and security services. The implementation of these solutions in both areas at the same time will be the most effective approach to manage the assets in the most effective way. Implemented IT solutions support rational planning, collecting, storing and using assets. Logistics management should be integrated with finances and Human resources, which facilitates delivery of necessary assets in tight quantity, quality, place and time for competitive price. This will influence achieving set aims (fulfilling tasks) in time of peace, crisis and war. Presented solutions set general directions for informatization and involve implementation of the latest technologies (software, applications, hardware, and computer networks) and IT security. As the result the Integrated Multilevel IT Systems for Logistics, Finance and HR should be built. This system with applied planning, analytical and evaluation applications operates in real time and facilitate information exchange with systems of national economy, NATO and EU. The base of Integrated Multilevel IT Systems for Logistics, Finance and HR is the reliable coding and identification system for all assets used and in stock. With the coding system it is possible to organize electronic shopping which help prevent corruption. The distance learning (e-learning) is another effective solution for logistics, finance and HR. Presented possibilities of implementing new IT solutions for logistics, finance and HR are not the only possibilities new IT solutions offer. The presented ones should serve as an inspiration for decision-makers to further actions, theoretical research and practical steps. The conducted research proved that new IT solutions influence better performance of logistics, finance and HR for defense and security services. It should also be indicated that implementation of new solutions for defense and security services is long organizational and intellectual process. It needs financial means, well prepared experts at single organizational levels where these solutions are being implemented.
Keywords: Informatization; IntegratedMultilevel IT Systems; coding; electronic shopping; distance learning; 368